2015
DOI: 10.1590/0103-6440201300166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Rotary Files Combined with Different Irrigation Needles on Apically Extruded Debris

Abstract: <p>The aim of this study was to compare the apically extruded debris associated with ProTaper Next and OneShape Apical files using two different irrigation needles, open-ended and closed-ended (Max-I-Probe). Forty-eight mandibular premolars were assigned to four groups (n=12) as follows: Group PTN-SN: Root canal was prepared with ProTaper Next (PTN) and irrigated with open-ended standard needle; Group PTN-MP: Root canal was prepared with PTN and irrigated with Max-I-Probe; Group OSA-SN: Root canal was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…However, there was no statistically significant difference in the pain levels between both groups at all the post-operative time points, this was in agreement with Uzunoglu et al (2015) (28) who reported no difference in the apical extrusion but in contrast to Altundasar et al (2011) (7) who reported higher apical extrusion by the end-vented needle than the side-vented needle.…”
Section: Root Canal Treatment Was Completed In a Single-visit As Wongsupporting
confidence: 88%
“…However, there was no statistically significant difference in the pain levels between both groups at all the post-operative time points, this was in agreement with Uzunoglu et al (2015) (28) who reported no difference in the apical extrusion but in contrast to Altundasar et al (2011) (7) who reported higher apical extrusion by the end-vented needle than the side-vented needle.…”
Section: Root Canal Treatment Was Completed In a Single-visit As Wongsupporting
confidence: 88%
“…However, this was in contrast with the results of Uzunoglu et al (2015) (28) who reported no difference in the apical extrusion between end-vented and side-vented needles, this may be due to using the needles at a greater distance from the apex.…”
contrasting
confidence: 89%
“…Most in vitro extrusion studies do not attempt to simulate adjacent vital pulp or periapical tissues (3,14,15). Yet, these tissues act as a natural barrier preventing or diminishing debris extrusion and therefore, such results should not be directly extrapolated at the dental clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Root canal irrigation is an important part of canal preparation for the removal of bacteria, debris and necrotic tissue, especially from root canal areas previously untouched by instrumentation (1). In an irrigant is not used, no significant debris extrusion occurs, but during root canal irrigation there is considerable extrusion of material (2,3). Debris extrusion depends on several factors, including the apical anatomy, type and size of the irrigation needle, needle placement depth, apical preparation size and taper, and the instrumentation technique (4).…”
Section: Introductionmentioning
confidence: 99%